2020
DOI: 10.1097/ppo.0000000000000493
|View full text |Cite
|
Sign up to set email alerts
|

Moving Immunotherapy Into Early-Stage Lung Cancer

Abstract: Blockade of the programmed cell death 1 immune inhibitory pathway has revolutionized the treatment of advanced non–small cell lung cancer and led to significant improvements in overall survival. In contrast, early-stage surgically resectable lung cancer has had few treatment advances in many years and continues to be associated with a high risk of relapse despite apparent curative resection. In this review, we discuss the many ongoing efforts to incorporate programmed cell death 1 pathway blockade into the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Clinical studies showed that immunotherapy has a good effect on advanced NSCLC ( Garon et al, 2019 ). Moreover, early-stage surgically respectable LUAD may benefit from Immunotherapy ( Linehan and Forde, 2020 ). Bioinformatics analysis of immune checkpoint expression levels and immune cell infiltration is warranted to help predict immunotherapy efficacy and facilitate precision treatment of es-LUAD.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies showed that immunotherapy has a good effect on advanced NSCLC ( Garon et al, 2019 ). Moreover, early-stage surgically respectable LUAD may benefit from Immunotherapy ( Linehan and Forde, 2020 ). Bioinformatics analysis of immune checkpoint expression levels and immune cell infiltration is warranted to help predict immunotherapy efficacy and facilitate precision treatment of es-LUAD.…”
Section: Introductionmentioning
confidence: 99%
“…According to the size, shape, progression rate, and imaging characteristics of pulmonary nodules, the benign and malignant properties and etiology of pulmonary nodules can be predicted. Pulmonary nodules less than 10 mm have only a 1% possibility of malignancy, while the malignant degree of pulmonary nodules reaching 20 mm is greatly increased [ 24 ]. If pulmonary nodules are detected, attention should be given to the nature of the nodules, and it is necessary to actively look for the cause and perform a differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Because of the limitation of adjuvant chemotherapy, MPR has been rare in lung cancer, with rates of 2%–7%, 12 , 14 , 15 , 16 , 17 but the incidence of MPR of neoadjuvant immunotherapy improved significantly, with a rate of 14%–83%. 18 , 19 The application of MPR has extended to the surrogate endpoint of neoadjuvant targeted therapy and immunotherapy clinical trials, such as the CTONG1103, 20 CheckMate‐159, 21 Nadim, 22 study, and so forth. Several trials have correlated MPR with DFS and OS in NSCLC.…”
Section: Rationale For Neoadjuvant Immunotherapy In Nsclcmentioning
confidence: 99%
“…In the era of targeted immunotherapy, the concept of MPR has been widely used, although its rationality has been questioned 13 . Because of the limitation of adjuvant chemotherapy, MPR has been rare in lung cancer, with rates of 2%–7%, 12,14–17 but the incidence of MPR of neoadjuvant immunotherapy improved significantly, with a rate of 14%–83% 18,19 . The application of MPR has extended to the surrogate endpoint of neoadjuvant targeted therapy and immunotherapy clinical trials, such as the CTONG1103, 20 CheckMate‐159, 21 Nadim, 22 study, and so forth.…”
Section: Rationale For Neoadjuvant Immunotherapy In Nsclcmentioning
confidence: 99%